Anxiolytic potential of 1-methyl/4-(tert-butyl)-2'-(cycloalkyl/hetaryl)-6'H-spiro[piperidine/cycloalkane-4,5'/1,5’-[1,2,4]triazolo[1,5-c]quinazolines] - Antypenko, L.; Shabelnyk, K. P.; Antypenko, O. P.; Шабельник, Костянтин Петрович; Антипенко, Олексій Миколайович (My University, 2025)
The aim of the work. Systematically analyze the binding affinities of a series of compounds targeting GABA(A) receptors, identify structural characteristics that correlate with high receptor binding efficiency, and develop structure-activity relationship (SAR) insights to guide future ligand design for pharmaceutical development.